2020
DOI: 10.3389/fenvs.2020.00083
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic Microfiber and Microbead Exposure and Retention Time in Model Aquatic Species Under Different Exposure Scenarios

Abstract: Synthetic microfibers have been reported in most aquatic environments and represent a large proportion of environmental microplastics. However, they remain largely underrepresented in microplastic ecotoxicity studies. The present study aims to investigate particle interaction with, and retention time in, aquatic organisms comparing microfibers, and microbeads. We used brine shrimp (Artemia sp.) and fish (Gasterosteus aculeatus) as invertebrate and vertebrate models, respectively. Organisms were exposed to a mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 59 publications
(73 reference statements)
4
14
0
Order By: Relevance
“…exposures. The absence of MPs in most fish samples is explained by the short particle retention time in three-spined stickleback (<48 h; Bour et al, 2020): the last contamination before fish were sampled was performed more than 48 h and total egestion of MPs could be expected.…”
Section: Discussion Experimental Trophic Chainmentioning
confidence: 99%
“…exposures. The absence of MPs in most fish samples is explained by the short particle retention time in three-spined stickleback (<48 h; Bour et al, 2020): the last contamination before fish were sampled was performed more than 48 h and total egestion of MPs could be expected.…”
Section: Discussion Experimental Trophic Chainmentioning
confidence: 99%
“…Reports of microplasticrelated risks for marine organisms have, for the most part, been associated with their uptake, and specifically direct ingestion of microplastic items (GESAMP, 2019). Other pathways, however, such as passive uptake through the gills (Bour et al, 2020a) or via trophic transfer from prey items (Santana et al, 2017;Miller et al, 2020) have been demonstrated in controlled laboratory experiments. Thus, similar to other contaminants (Blanco et al, 2018;Amoroso et al, 2020;Hassell et al, 2020), depuration is a major factor influencing the potential effects of microplastics following ingestion.…”
Section: Introductionmentioning
confidence: 99%
“…Synthetic microfibres have been shown to be ingested by many aquatic species, including zooplankton, polychaetes, bivalves and crustaceans (Alnajar et al, 2021;Chinfak et al, 2021;Mateos-C ardenas et al, 2021;Bour et al, 2020;Avio et al, 2020;Jemec et al, 2016), deep-sea organisms (Pereira et al, 2020;Taylor et al, 2016;Murray and Cowie, 2011), marine, freshwater and farmed fish (Savoca et al, 2021;Avio et al, 2020;Halstead et al, 2018;Horton et al, 2018) and birds (Bourdages et al, 2021;Hamilton et al, 2021;Coughlan et al, 2020). Exposure to microfibers can affect growth, reproduction and survival of water fleas and amphipods (Ziajahromi et al, 2017b).…”
Section: Fate and Environmental Effects Of Microfibres From Textilesmentioning
confidence: 99%
“…This can obviously be a harmful effect in any animal that ingests microfibres. Bour et al (2020) compared the toxic effects of high concentrations of polyester microfibres (500 μm long) and polyethylene microbeads (27)(28)(29)(30)(31)(32) μm) in brine shrimp (Artemia sp.) and fish (Gasterosteus aculeatus), invertebrate and vertebrate aquatic species, respectively.…”
Section: Fate and Environmental Effects Of Microfibres From Textilesmentioning
confidence: 99%
See 1 more Smart Citation